SIMULATION OF TRAFFIC MANAGEMENT AND ENGINEERING TO IMPROVE THE PERFORMANCE OF THE FIVE POINT INTERSECTION ON JALAN KEPUTIH SURABAYA - Desi Aura Lestari; Kurnia Hadi Putra; Theresia Maria Chandra Agusdini (Journal Innovation of Civil Engineering)
The five-point intersection on Keputih Street is one of the unsignaled intersections in the city of Surabaya with traffic problems. At certain times, especially rush hour, traffic problems will occur. At 07.00 WIB it was seen that several drivers were trying to cut through the traffic jam by squeezing in between other vehicles, this was done by road users to avoid long queues of vehicles. Queues can be approximately 1.2km long and the surrounding existing conditions are commercial or shopping areas, housing with several sides of the road used as a means for vehicles to stop or park as an additional congestion factor. Thus, there is a need for management planning and traffic engineering to improve the quality of intersections in serving road users. The method used for data analysis is based on existing data obtained directly from the field and processed according to PKJI 2023. The results obtained were that the degree of saturation at the intersection was much different before and after the traffic engineering planning was carried out. Projection results with the installation of traffic light signs and geometric widening of Keputih Tegal, the degree of saturation value obtained was 0.78 where previously DJ = 0.98 0.85.